Trabalho e carreira docente nos Institutos Federais de Educação, Ciência e Tecnologia - Costa, Elen de Fátima Lago Barros (Universidade Federal de São Carlos, 2016)
To analyze the recent history of Brazil, it finds that the periods of two terms of Luiz Inacio Lula da Silva´s government (2003-2010) are emblematic regarding the political and economic context, the educational paradigm assumed and the resulting reforms of this new model and consequently the changes in republican institutions, legitimating spaces that materialize these policies. In the Lula´s government, among other actions, is the core formulating a new institutional framework of Vocationa and Technological Education, geared to meet even more the needs not only of this new cycle of the economy, as well as a large portion of the population that needed professional qualification of technical level. It would be interesting also that this service could be effected by an institution that offers, in the same space, levels and modes of different teachings. Answering to such demands, the Federal Government created and expanded a new network of vocational and technical education "singular and plural curricular" – Federal Institutes of Education, Sciense and Thecnology (IFET's). In this way, the objective of this research is to analyze the changes in career and in teacher’s workon IFET's, after the creation / expansion of new network of Vocational and Technological Education, which began in the country, from the first term of the government of Luis Inacio Lula da Silva and consolidated in the government of Dilma Roussef. It was defined as specific objectives: to analyze the goals, principles and purposes of IFETs, the intended to effected by establishing a relationship between the current legislation and the empirical field, supported by data and voice of the subjects; verify the specifics of the expansion of IFET in Brazil and Maranhão, studying their links with politics and with local production arrangements; analyze what level of understanding of teachers about changes in the field of vocational and technological education, as well as its relations with the current economic climate; verify that the transformation to IFET promoted and / or promote changes in the work of the teachers who work in this institution, if these teachers perceive them and how they deal with them. As empirical field defined the Federal Institute of Maranhão (IFMA).Our hypothesis is that the expansion of vocational education policy and technology adopted in Brazil, from the first commandment of the Lula government and to the present day, follows some unique characteristics, characterized by a mass certification of "invisible of the lula", so, a large portion of the working class with little education and / or professional qualification, concentrated in the poorest regions of the federation, on the outskirts of large urban centers of the country. In addition, we assume that the changes implemented at the institutional level have modified the teacher's work with regard to the way of doing science, in the development of their professional activities, as well as their working hours. To confirm this hypothesis and assuming that the organization of production in the capitalist mode is marked by contradictory aspects, this research took advantage of dialectical and historical reference, in particular, expressing Marx´s studies and authors of today's Marxist matrix, believing that this framework will bring the necessary support so that this phenomenal appearance and contradictory to be unveiled.
Keywords: Trabalho docente; Educação profissional e tecnológica; Institutos federais; Teacher's work; Professionaland technological education; Federal institutes; CIENCIAS HUMANAS::EDUCACAO